Peptic Ulcer Disease - Seung Han Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2025)
Although the incidence and complications of peptic ulcer disease have declined, Helicobacter pylori infection and nonsteroidal anti-inflammatory drug use remain key risk factors. Advances in proton pump inhibitors and potassium-competitive acid blockers have improved treatment outcomes. However, increasing antibiotic resistance has reduced the efficacy of the standard therapies for H. pylori eradication, necessitating the development of new approaches such as novel antibiotic combinations and bismuth-based regimens. Future studies should emphasize tailored strategies to address resistance and the development of innovative anti-ulcer therapies to enhance eradication and prevention efforts.